Usefulness of the Infant Driven Scale in the early identification of preterm infants at risk for delayed oral feeding independency. (December 2017) - Giannì, Maria Lorella; Sannino, Patrizio; Bezze, Elena; Plevani, Laura; Esposito, Chiara; Muscolo, Salvatore; Roggero, Paola; Mosca, Fabio
Abstract: Background: Very preterm infants frequently experience difficulties in achieving feeding independency. The availability of feeding assessment instruments has been recommended to evaluate an infant's readiness for oral feeding and enable preterm infants' caregivers to document each infant's feeding readiness and advancements. Aims: To investigate the implementation of the Infant Driven Scale in neonatal intensive care units and to identify a cut off value associated with delayed feeding independency. Study design: Prospective, observational, single-centre study. Subjects: A total of 47 infants born at a gestational age ≤ 32 weeks, consecutively admitted to a tertiary neonatal unit between July 2015 and March 2016. Outcomes measures: The infant's feeding readiness and the postmenstrual age at achievement of feeding independency. Results: Mean postmenstrual age at feeding independency was 35.6 ± 1.34 weeks. A linear regression analysis showed that a score ≤ 8 at 32 weeks of postmenstrual age was associated with a delay of 1.8 weeks in achieving feeding independency. Conclusion: The Infant Driven Scale appears to be a useful additional instrument for the assessment of preterm infants' oral feeding readiness and the early identification of the infants at risk for delayed feeding independency. Highlights: Preterm infants frequently experience feeding difficulties, thus contributing to delayed growth and hospital discharge. A "cue-based" oral feeding approach promotes the development of preterm infants' oral competencies. The Infant Driven Scale allows the early identification of the infants at risk for delayed feeding independency. Health care professionals should place efforts on implementing the Infant Driven Scale in neonatal intensive care units.